Review of the Prabhasa Moore, 1878 genus-group (Lepidoptera, Erebidae, Arctiinae) - Dubatolov, Vladimir V.; Volynkin, Anton V.; Kishida, Yasunori (Zootaxa, 2018)
The Prabhasa Moore, 1878 genus-group is reviewed. The male and female genitalia of Prabhasa venosa Moore, 1878, the type species of the genus, are described and illustrated for the first time. Two new genera, Macohasa Dubatolov, Volynkin & Kishida, gen. nov. and Chinasa Dubatolov, Volynkin & Kishida, gen. nov. and two new species, Macohasa cernyi Dubatolov, Volynkin & Kishida, sp. nov. and Chinasa sapa Dubatolov, Volynkin & Kishida, sp. nov. are described for Prabhasa venosa sensu authors. Seven new combinations are established: Zadadra plumbeomicans (Hampson, 1894), comb. nov., Zadadra monastyrskyi (Dubatolov, 2012), comb. nov., Macohasa orientalis (Hampson, 1905), comb. nov., Macohasa tetraspila (Černý, 2009), comb. nov., Macohasa dimorpha (Hampson, 1918), comb. nov., Chinasa costalis costalis (Moore, 1878), comb. nov. and Chinasa costalis bicoloriceps (Strand, 1916), comb. nov.